Hepatoprotective Effect of Extra Virgin Olive Oil and Apple Cider Vinegar in Type-2 Diabetic Rat Model - Ruqaiyya Nazir; Muniza Saeed; Ghulam Mustafa; Seher Naeem; Hifza Noor Lodhi; Sehrish Ijaz (Proceedings, 2024)
Introduction: Type-2 diabetes mellitus, a major public health problem, is caused by insulin resistance. In diabetics, chronic hyperglycemia results in formation of reactive oxygen species. Oxidative stress in diabetic patients is responsible for hepatic damage because it causes activation of several pro-inflammatory mediators in liver. Hepatic complications of diabetes include fatty liver disease, necrosis, cirrhosis, carcinoma and liver failure.